2022
DOI: 10.1016/j.eujim.2022.102102
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements intake during the second wave of COVID-19 pandemic: A multinational Middle Eastern study

Abstract: Introduction Despite the controversy about the benefits of dietary supplements in treating or preventing COVID-19, their use has increased worldwide even with the introduction of relevant vaccines. Thus, this study aimed to investigate the perception of Middle Eastern Arab publics of dietary supplements as prophylactic or therapeutic agents against COVID-19, and their consumption during the second wave of COVID-19 pandemic. Methods A validated, pilot tested online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…Other inappropriate recommendations made by the CPs included confirmation that the patient had COVID-19 without prior testing, informing the patient that the PCR test is not mandatory, assuring the patient is not infected with COVID-19 and prescribing either an antimicrobial drug or dietary supplements. Despite the controversy about the benefits of dietary supplements in treating or preventing COVID-19 infection [ 40 – 43 ], some encountered pharmacists claimed that dietary supplements are essential to boost the patient’s immunity. Thus, exposing the patient to falsified hyperbolic health claims, lacking rigorous evidence to support their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Other inappropriate recommendations made by the CPs included confirmation that the patient had COVID-19 without prior testing, informing the patient that the PCR test is not mandatory, assuring the patient is not infected with COVID-19 and prescribing either an antimicrobial drug or dietary supplements. Despite the controversy about the benefits of dietary supplements in treating or preventing COVID-19 infection [ 40 – 43 ], some encountered pharmacists claimed that dietary supplements are essential to boost the patient’s immunity. Thus, exposing the patient to falsified hyperbolic health claims, lacking rigorous evidence to support their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are no specific randomized controlled trials (RCTs) on vitamin supplementation in the prevention or treatment of COVID-19 infection. Therefore, clinical trials are needed to confirm the role of these supplements in COVID-19 prevention and treatment [ 64 , 65 ]. The use of nutraceuticals in post-COVID syndrome is currently under study.…”
Section: Nutraceuticals and Dietary Supplements Against Covid-19 Dise...mentioning
confidence: 99%
“…However, not much data supported the intake of oral vitamin C supplements to increase immunity ( 13 ). Several studies have shown that oral vitamin C supplementations since COVID-19 have increased ( 15 , 16 ). However, dietary supplements in those studies against COVID-19 were not evidence-based.…”
Section: As Daily Supplements–prevention Measuresmentioning
confidence: 99%